Folding of granulin domains. Issue 3 (14th March 2018) - Dastpeyman, Mohadeseh; Smout, Michael J.; Wilson, David; Loukas, Alex; Daly, Norelle L.
Abstract: Granulins are a family of protein growth factors that are involved in a range of biological functions, including wound repair, inflammation, and tumor growth. They are often expressed as part of large precursor proteins containing multiple granulin domains. Individual granulin domains are characterized by a conserved arrangement of 12 cysteine residues that form six disulfide bonds. Despite the conservation of the cysteine residues, there is significant sequence variation between granulins from different species. The initial structure determined for this family indicated the presence of a well‐defined structure with a laddered arrangement of the six disulfide bonds and a β‐hairpin stack. However, subsequent studies have shown the structure‐function relationships of granulins are quite complex. Recent studies have indicated some granulins might have potential as wound healing agents, and studies aimed at understanding the structure‐function relationships of this family are likely to enhance this potential in drug design. This review provides an overview of the structure‐based studies of granulins, including the folding of truncated peptides derived from granulins from different species. Abstract :